Using an Embedded Multi User Inverse Kinematic Solver for Intuitive Modeling and Simulation. (November 2022) - Schönböck, Johannes; Witteveen, Wolfgang; Lonauer, Paul; Kovacs, Carrie; Augstein, Mirjam; Pöchacker, Stefan; Oberpeilsteiner, Stefan
Abstract: Following the vision of Industry 4.0, manufacturers started to break down products into subsystems, each of which is developed and supplied by different suppliers to tackle the increasing complexity of product development (e.g., in vehicle, machine or plant construction). This process needs to be supported by intuitive Computer-Aided Design (CAD) tools and virtual modeling and simulation environments to effectively meet the challenges of increasingly complex product development. Therefore, in this paper, we present some outcoming of a research project called DisMoSim (Dis tributed Mo deling and Sim ulation), which proposes an intuitive virtual environment for modeling and simulation that embeds a Multi User Inverse Kinematic Solver (MUKS). The MUKS allows (i) individual subsystems to be tested intuitively, i.e., Rapid Testing (RT), and (ii) people not yet familiar with a subsystem to understand it easily and quickly through simple kinematic actions, i.e., Rapid Understanding (RU), without unnaturally interrupting the modeling process. Finally, (iii) the MUKS enables subsystems to be easily assembled into complete systems, i.e., Rapid Assembling (RA), by means of a so-called snapping-point mechanism which supports the complex process of aligning and assembling different subsystems. To evaluate these capabilities, we present the results of a user study conducted with 20 participants. Special attention has been given to the embedded MUKS in contrast to existing approaches known from common CAD and simulation software. Thus, we demonstrate the practicability, usability, and versatility of our approach. Highlights: Finding modeling and simulation errors in CAD models is cumbersome with current tools. CAD tools need intuitive means for testing during modeling. Inverse kinematic solvers allow for rapid prototyping and testing in CAD systems. New user interface and interaction paradigms ease interaction with CAD tools.